Application of e-PTFE Frontalis Suspension in the Treatment of Congenital Ptosis in Children - Ma, Ling; Zhang, Lei; Liu, Zhen; Wang, Dandan; Li, Yibao; Zhang, Chengyue (Frontiers in Surgery, 2022)
Purpose: To analyze the value of expanded polytetrafluoroethylene (e-PTFE) frontalis suspension in children with congenital ptosis. Methods: Eighty clinical cases of children with congenital ptosis from October 2019 to October 2021 were randomly selected from our hospital. All children were divided into the observation group (n=44) treated with e-PTFE frontalis suspension and the control group (n=36) treated with frontalis flap suspension according to the treatment procedure. Comparison of eyelid condition [palpebral fissure height, distance from eyelid margin to corneal light reflection point (MRD), eyelid closure time], ocular surface status (corneal fluorescein staining scores, tear film breakup time, surgical eye lacrimal river height, sehirmer test I), frontal muscle strength of affected side, cosmetic results and complications in both groups at 1, 6 and 12 months postoperative follow-up. Results: At 1, 6 and 12 months after surgery, there was no significant difference in terms of palpebral fissure height and MRD between both groups (P > 0.05); After surgery, the eyelid closure time was shorter in the observation group than in the control group (P < 0.05). At 1, 6 and 12 months after surgery, the corneal fluorescein staining scores were lower in the observation group than in the control group (P < 0.05); At 6 and 12 months after surgery, the tear film breakup time was longer and the surgical eye lacrimal river height was higher in the observation group than in the control group (P < 0.05); At 1, 6, and 12 months after surgery, there was no significant difference in sehirmer test I between both groups (P < 0.05). At 1, 6 and 12 months after surgery, the frontal muscle strength of affected side was higher in the observation group than in the control group (P < 0.05). Conclusion: The surgical and cosmetic results of e-PTFE frontalis suspension and frontalis flap suspension applied to congenital ptosis are comparable, but the former has the advantage of faster postoperative recovery, better ocular surface status, less frontali muscle strength damage and fewer complications.